The JUST GROW framework: conceptualizing how city regions can govern urban agriculture for equity and sustainability - Baur, Patrick; Jennings, Rose; Aliu, Sheriff; Calo, Adam J.; Farhangi, Mosen; He, Yukun; Kanki, Kiyoko; Koch, Ann-Kristin; Kiyoyama, Yohei; Martin, Michael; Sabir, Beste; Schröter, Barbara; et al. (Frontiers in Sustainable Food Systems, 2025)
City regions hold much potential for advancing sustainable and just food system transformations. A mosaic of models for producing more food in and around cities is emerging that promises shorter supply chains, increased food access, plant-based solutions and robust community resilience. Models for urban agriculture range from backyard and community gardens to rooftop farms to plant factories, representing tremendous diversity in the cropping systems, technologies, skills, and organizational forms used to grow food. Amidst this flourishing, concerns over inequitable distributions of the benefits and risks of expanding urban agriculture underscore the need to center justice in determining the right mix of models. City regions need innovative governance approaches to strategically, sustainably, and equitably manage this emerging mosaic at the city region scale and considering its full social-ecological ramifications. The JUST GROW framework addresses this need by incorporating three interlinked principles of justice into a comprehensive governance process of collective knowing, inclusive deliberation, and intentional action. We offer strategies for building collaborative capacities among community, government, and research stakeholder groups to cocreate indicators and invest in the data infrastructure needed to measure outcomes that matter for sustainability and equity. Our framework also creates a pathway to proactively construct responsibility to act on this knowledge bank by aligning authority, capacity, and motivation within representative governance networks. The long term goal of the JUST GROW framework is to build a process for food producers, urban planners, municipal agencies, community groups, and civil society organizations to help city region food systems (CRFS) better provide key benefits from urban agriculture—including positive environmental impacts, supporting vibrant food cultures, land access, livelihoods, and food security—for all people now and into the future.